2017
DOI: 10.23863/kalem.2017.76
|View full text |Cite
|
Sign up to set email alerts
|

8. Sınıf Öğrencilerinin Temel Eğitimden Orta Öğretime Geçiş (TEOG) Sınavına İlişkin Algılarının Metaforlar Aracılığıyla İncelenmesi

Abstract: Öz 8. sınıfta yapılan TEOG sınavı, Türk Millî Eğitim Sistemi'nde birçok öğrencinin akademik yaşamına nasıl devam edeceğini belirleyen ve öğrencilerin hayatlarında önemli bir yere sâhip olan ilk karşılaştıkları merkezî sınavdır. Öğrencilerin TEOG sınavını ne şekilde algıladıkları hem kaygı durumlarını hem de motivasyon düzeylerini ortaya koymada ve etkili biçimde rehberlik hizmetlerini yürütmede önemli bir veri kaynağıdır. Bu araştırmanın temel amacı 8. sınıf öğrencilerinin TEOG sınavına yönelik algılarının met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
13

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
0
5
0
13
Order By: Relevance
“…However, the "anxiety and stress that I experienced" stimulus was scaled as significant by all of the students. Some metaphorical research (Duban & Arısoy, 2016;Karadeniz et al, 2014;Koçak et al, 2017) showed that students' perceptions about secondary school entrance exams were mostly associated with stress, anxiety, hopeless, and death. Even though these studies did not reveal the significance level of this problem, they can be evaluated as the explanator of students' judgments about this stimulus.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the "anxiety and stress that I experienced" stimulus was scaled as significant by all of the students. Some metaphorical research (Duban & Arısoy, 2016;Karadeniz et al, 2014;Koçak et al, 2017) showed that students' perceptions about secondary school entrance exams were mostly associated with stress, anxiety, hopeless, and death. Even though these studies did not reveal the significance level of this problem, they can be evaluated as the explanator of students' judgments about this stimulus.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…One of the problems in the transition system to secondary education in Turkey is increasing need for out-ofschool resources such as cram and private schools (MoNE, 2010;Turkish Education Association [TED], 2010;Şad & Şahiner, 2016). Another problem is the negative consequences of entrance examinations on students' psychology such as distress and anxiety (Koçak, Doğan-Gül, Gül, & Çokluk-Bökeoğlu, 2017;Duban & Arısoy, 2016;Karadeniz, Er, & Tangülü, 2014;MoNE, 2010). Moreover, many teachers feel increased pressure and under risk, while trying to increase students' success (Atila & Özeken, 2015;Buyruk, 2014).…”
Section: **Amentioning
confidence: 99%
“…Ancak, bu araştırmaların genel anlamda merkezi sistem sınavları üzerinde değil, daha çok herhangi bir merkezi sistem sınavı (TEOG, SBS, KPSS, Üniversite Sınavı, vb.) ile ilişkilendirilerek gerçekleştirildikleri görülmüştür (Demir, Kutlu ve Özdemir, 2016;Duban ve Arısoy, 2017;Güngör-Aytar ve Kurtoğlu-Karataş, 2017;Güven ve Dak, 2017;Karadeniz, Er ve Tangülü, 2014;Karaşahinoğlu, 2015;Koçak, Doğan-Gül, Gül ve Çokluk-Bökeoğlu, 2017;Tekinarslan, 2013). Bu haliyle, araştırma alanyazınında, merkezi sistem sınavlarının genel bir isim altında değil de, ayrı ayrı şekilde (TEOG, SBS, KPSS, Üniversite Sınavı, vb.)…”
Section: Sınava İlişkin Metaforlarunclassified
“…Çalışmada, metaforların tümü frekans büyüklüğüne göre sıralanarak Tablo 1'de gösterilmiştir. (Demir, Kutlu ve Özdemir, 2016;Duban ve Arısoy, 2017;Güven ve Dak, 2017;Karadeniz, Er ve Tangülü, 2014;Karaşahinoğlu, 2015). Türkiye'deki merkezi sistem sınavları pratiğine bakıldığında, sınav maratonunun başlangıcının ilkokul çağına kadar inmiş olduğu görülmektedir (Dönmez, 2008).…”
Section: Bulgularunclassified
See 1 more Smart Citation